Sublethal effects of spirodiclofen on biological and demographic parameters of the citrus leprosis mite Brevipalpus yothersi (Acari: Tenuipalpidae) - Amaral, Ingrid [UNESP]; Melville, Cirano C [UNESP]; Rocha, Claudiane M [UNESP]; Della Vechia, Jaqueline F [UNESP]; Prado, Thais J [UNESP]; Andrade, Daniel J [UNESP] (Wiley, 2020)
BACKGROUND: Brevipalpus yothersi Baker is one of the main vectors of citrus leprosis. Knowing the biology of this mite species when under chemical control is extremely important to understand its population dynamics, and then to solve problems of management of this pest. Therefore, we assessed the effects of one sublethal dose of spirodiclofen (0.48 ppm) on biological and demographic parameters of B. yothersi under laboratory and greenhouse conditions, comparing them with non-exposed mite population. RESULTS: Under laboratory conditions, where citrus fruits were used as a substrate, the duration of developmental stages (pre-egg-laying and egg-laying) and mite longevity showed no differences between treatments. However, the number of laid eggs increased in acaricide-treated fruits. In the greenhouse experiment, where citrus plants were used as a substrate, the instantaneous growth rate (ri) of mites was positive in all untreated plots. In contrast, in treated plants, ri was negative in 12 experimental units, and mite populations were suppressed in five of them. Moreover, mite population dynamics had a positive ri in three treated plants. CONCLUSIONS: Spirodiclofen sublethal dose had no negative effect on the offspring of B. yothersi females. However, it is not safe for citrus leprosis mite since it may increase egg number per female in some conditions. Biological and demographic differences could influence mite population dynamics in the field, requiring appropriate management strategies to improve citrus leprosis control. © 2019 Society of Chemical Industry.
Keywords: CiLV-C; Citrus sinensis; fertility life table; flat mites